Kepercayaan Diri Remaja Penyandang Tunarungu Berprestasi - Ridha Fadilah Azmi; Rahmi Lubis (Universitas Medan Area, 2023)
This study aims to find out how and what factors influence the self-confidence of deaf adolescents in achieving. This study uses a qualitative method with a phenomenological approach. The number of respondents to this study was 3 people with the characteristics of deaf adolescents who excel in the arts at SLB Melati Aisyiyah. Data collection techniques using interview and observation methods. The results of the study explained that the three respondents had achievements in the arts. The first and second respondents have confidence in their own abilities, are optimistic, and are objective. However, the two respondents are less responsible, rational and realistic. The third respondent has confidence in his own abilities, is optimistic, objective, and responsible. However, less rational and realistic. The three respondents felt proud of their achievements and expertise, had positive experiences, received social support and approval, and had competence and achievements. However, the three respondents did not respond when facing problems.